2008
DOI: 10.1158/0008-5472.can-08-2132
|View full text |Cite
|
Sign up to set email alerts
|

The Melanoma-Associated Antigen A3 Mediates Fibronectin-Controlled Cancer Progression and Metastasis

Abstract: Tumor cells frequently exhibit decreased adhesiveness due to failure to deposit stromal fibronectin (FN), permitting more rapid proliferation, migration, invasion, and metastasis. Although up-regulation of FN has been noted in gene profiles of carcinomas compared with normal tissue, reduced FN expression has been described at the peripheral margins of invading tumors. In this study, we investigate the role of FN in cancer behavior. Using human thyroid carcinoma cells with stably down-regulated FN, we performed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
103
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 40 publications
10
103
0
Order By: Relevance
“…Nevertheless, in the last years compelling evidence has accumulated suggesting that individual MAGE proteins could behave in specific pathways critical for tumor progression. [30][31][32][33][34] We previously demonstrated that MageA2 is a relevant player in favoring chemoresistance to p53 bearing human melanoma cells. Here, we analyze the role of MageA2 as regulator of another important tumor-suppressive mechanism, namely cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in the last years compelling evidence has accumulated suggesting that individual MAGE proteins could behave in specific pathways critical for tumor progression. [30][31][32][33][34] We previously demonstrated that MageA2 is a relevant player in favoring chemoresistance to p53 bearing human melanoma cells. Here, we analyze the role of MageA2 as regulator of another important tumor-suppressive mechanism, namely cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Previous studies in a thyroid carcinoma model have suggested that selected MAGE-A genes might control fibronectin-mediated tumor progression. 42 Notably, MAGE-A11, also characterized by a putatively specific intranuclear location, has been shown to coregulate androgen receptor-mediated transcriptional activity. 43,44 Most interestingly, MAGE-A gene expression has been found to be correlated with genome-wide demethylation, 45 frequently representing an early event during carcinogenesis, associated with hypermethylation of defined tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, Jurkat cells, which are sensitive to ABT-263, had the highest expression of CD99 in our panel. MAGEA3 (increased in resistant leukemia/lymphoma lines) has been shown to contribute to fibronectin-mediated cancer progression through enhanced tumor growth (49).…”
Section: Discussionmentioning
confidence: 99%